Readiness of People Serving Probation to Help Others - Klymkiv, Roksolana (Psychological Prospects Journal, 2016)
The article centers around the necessity of psychological work for people under the care of the new body probation with components forming prosocial relationships. The work must go alongside with their involvement in volunteer projects. The level of readiness for altruism is concerned to people serving probation as the final stage of their program of psychological support. Application of psychodiagnostic methods “Altruism – Nonaltruism” (J. Slivak). The choice of technique was due to its adaptation to the Ukrainian cultural realities, high validity and reliability that allows us to determine the level of altruism − nonaltruism. Results of psychological diagnostic methods, their statistical processing showed the effectiveness of previous psychological correction work. The average level of readiness to altruism of respondents and its tendency to increase have been found. Sex differences in the nature of relationships between prosocial persons serving probation have been clarified. Men have higher indicator of readiness for the subject and activity-aid than women. Instead, women can easily convey ethical and empathic nature of social relationships. These sex differences determine the specific formation of further psychological correction work. Promising method of forming social relationships of prisoners is outlined. This method is dialogical analysis (together with a psychologist) behavioral patterns included in seventeen problems (problem situations) − method “Altruism − Nonaltruism”. The experience of psychological work with people serving probation dialogical method allows to add analysis by reinterpretation of problem situations during group sessions with people who undergo a psychological support program for prisoners. Keywords: altruism, forming, prosocial relationships, psychological correction work.